The External Environment-Strategic Planning Interface: U.S. Multinational Corporate Practices in the 1980s - Kennedy, Charles R. (Journal of International Business Studies, 1984)
This paper presents data collected by structured interviews concerning how external environment analysis and strategic planning are related in major U.S.-based multinational corporations. The research was also undertaken to ascertain why and the extent to which firms have formally institutionalized the external environmental functions since the Iranian revolution.